Daptomycin-Resistant Enterococcus Bacteremia Is Associated With Prior Daptomycin Use and Increased Mortality After Liver Transplantation. (22nd January 2022) - Lee, Rachael A; Goldman, Jason; Haidar, Ghady; Lewis, Jessica; Arif, Sana; Hand, Jonathan; La Hoz, Ricardo M; Pouch, Stephanie; Holaday, Eric; Clauss, Heather; Kaye, Keith S; Nellore, Anoma
Abstract: Background: Risk factors for acquisition of vancomycin-resistant Enterococcus (VRE) include immunosuppression, antibiotic exposure, indwelling catheters, and manipulation of the gastrointestinal tract, all of which occur in liver transplant recipients. VRE infections are documented in liver transplantation (LT); however, only one single center study has assessed the impact of daptomycin-resistant Enterococcus (DRE) in this patient population. Methods: We conducted a retrospective multicenter cohort study comparing liver transplant recipients with either VRE or DRE bacteremia. The primary outcome was death within 1 year of transplantation. Multivariable logistic regression analyses were performed to calculate adjusted odds ratios for outcomes of interest. Results: We identified 139 cases of Enterococcus bacteremia following LT, of which 78% were VRE and 22% were DRE. When adjusted for total intensive care unit days in the first transplant year, liver-kidney transplantation, and calcineurin inhibitor use, patients with DRE bacteremia were 2.65 times more likely to die within 1 year of transplantation (adjusted odds ratio [aOR], 2.648; 95% CI, 1.025–6.840; P = .044). Prior daptomycin exposure was found to be an independent predictor of DRE bacteremia (aOR, 30.62; 95% CI, 10.087–92.955; P < .001). Conclusions: In this multicenter study of LT recipients with Enterococcus bacteremia, DRE bacteremia was associated with higher 1-year mortality rates when compared with VRE bacteremia. Our data provide strong support for dedicated infection prevention and antimicrobial stewardship efforts for transplant patients. Further research is needed to support the development of better antibiotics for DRE and practical guidance focusing on identification and prevention of colonization and subsequent infection in liver transplant recipients at high risk for DRE bacteremia.